“Resilience picture Women Prisoners and Detention Class IIB Bangkalan”Thesis. - Devi Yeni Dikarini; Alifah Rahma Wati (Universitas Trunojoyo Madura, 2017)
This study aims to describe the resilience of women prisoners of Jail Class IIB Bangkalan. Thisstudy uses descriptive qualitative method on each subject that has been determined by purposive sampling, this study uses method of collecting data semi-structured interviews. Subjects in this study are a woman prisoner who experienced abuse cases that led to deaths and homicides. Female prisoners experience conflict sourced from within the jail and sourced outside of the jail, resulting in feelings of sadness, regret, depressed, even feel does not want anymore and crash. The results of this study indicate that women prisoners are able to overcome the problems faced in which these problems can lead to adversity and suffering every day. The ability of the female prisoners is the ability to resilience. To achieve the Traffic resilience of women prisoners also passed the seven dimensions: women prisoners are able to regulate negative emotions owned into a positive activity, impulse control women prisoners are able to withstand the desire arising from within himself, female inmates have a feeling of optimism for passing sentence at the jail and after coming out of the jail, clausal analyze the female inmates were able to analyze the causes of the problem either cause prisoners Imprisoned and during serving his sentence at the jail, women prisoners are able to empathize with a fellow inmate and able to empathize with the families left behind, self efficacy inmates have the ability to override the problems faced by the various ways that do, reaching out female prisoners were able to take the positive aspects or to take lessons from the problems faced. In addition to the seven dimensions of women prisoners to support the ability for resilience also supported by three factors: individual, family, neighborhood. So that each subject was able to achieve resilience and change the situation is better than before, and can take lessons from the events experienced.Keywords: Resilience, Women prisoners